Energy absorption capacity of steel fibre reinforced concrete - Barros, Joaquim A. O. (1999)
Steel fibre reinforced concrete (SFRC) is a cementitious material reinforced with a given content of discrete fibres. The use of SFRC in building construction has increased continuously due to its better mechanical properties, mainly, the energy absorption capacity. The energy dissipated to pull out the fibres from the cracked concrete is much higher than the energy dissipated to crack the concrete matrix. Therefore, the energy absorption capacity is the main material property benefited by fibre reinforcement. A servo-controlled equipment should be used to evaluate this property. The tests should be carried out using displacement control in order to obtain the post-peak force-displacement relationship (tensile strainsoftening branch). In the present work it is described the three point bending notched SFRC beam tests carried out using displacement control. Series of beams reinforced with 30, 60 and 90 kg/m3 of hooked ends steel fibres were tested. The main purpose of these tests was the evaluation of the fracture energy of SFRC. However, the energy evaluated from the force-displacement relationship registered in a test can be not only the energy dissipated in fracturing the concrete, but also the energy absorbed in compression deformation. For ductile materials like concrete reinforced with high content of fibres, the “fixed” points of the “Japenese Yok” bar may not remain fixed, which introduces extraneous deformations, leading to incorrect evaluation of the fracture energy. These factors were analysed in the present work in order to assess the appetence of the specimen dimensions and test procedures for evaluating the fracture energy of SFRC.